2021
DOI: 10.5539/ies.v14n2p44
|View full text |Cite
|
Sign up to set email alerts
|

Chatbot Development as a Digital Learning Tool to Increase Students’ Research Knowledge

Abstract: The research aimed to: 1) develop the chatbot; 2) evaluate its effectiveness; and 3) investigate its effects on students’ research knowledge. The sample consisted of 36 Thai university students. The research instruments consisted of: 1) the chatbot; 2) an evaluation form; 3) an effectiveness questionnaire; and 4) research tests. Data analysis used was mean, standard deviation, content analysis and a t-test. The findings indicated that: 1) the chatbot was evaluated by experts with the applicability at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 17 publications
(19 reference statements)
1
11
0
5
Order By: Relevance
“…The findings were consistent with previous researches. They were in line with Vanichvasin (2021) who found that the application of chatbot technology in education context to promote student knowledge of research yielded positive views of the chatbot as it created positive learning outcomes and provided better individualized learning experience while Winkler and Söllner (2018) reported that chatbots in education promised to have a significant good impact on learning success and satisfaction of students, which was in accordance with Alepsis and Virvou (2011) who reported that their study showed success in the use of conversational systems with high acceptance from both students and teachers that perceived the system as a very useful tool for health education and Preecha (2020) who reported that learning with an artificial intelligence chatbot was efficient as students can quickly find answers anytime and anywhere. Positive impact may stem from the researcher's experience in conducting this kind of research before but with different type of chatbot frameworks and platforms.…”
Section: Students' Perceptions Of Satisfactionsupporting
confidence: 66%
See 2 more Smart Citations
“…The findings were consistent with previous researches. They were in line with Vanichvasin (2021) who found that the application of chatbot technology in education context to promote student knowledge of research yielded positive views of the chatbot as it created positive learning outcomes and provided better individualized learning experience while Winkler and Söllner (2018) reported that chatbots in education promised to have a significant good impact on learning success and satisfaction of students, which was in accordance with Alepsis and Virvou (2011) who reported that their study showed success in the use of conversational systems with high acceptance from both students and teachers that perceived the system as a very useful tool for health education and Preecha (2020) who reported that learning with an artificial intelligence chatbot was efficient as students can quickly find answers anytime and anywhere. Positive impact may stem from the researcher's experience in conducting this kind of research before but with different type of chatbot frameworks and platforms.…”
Section: Students' Perceptions Of Satisfactionsupporting
confidence: 66%
“…Chatbots are useful in applications (Shawar & Atwell, 2007), which can be used as a tool to learn or study a new language, access an information system, visualize the contents of a corpus; and give answers to questions (Bayan, 2005). Benefits involve saving costs, time, and effort (Abdellatif et al, 2020), increasing interaction, active learning, and creative learning (Bii, 2013), promoting retention and engagement (Benotti et al, 2014), motivating students to learn (Benotti et al, 2014), and enhancing user satisfaction (Vanichvasin, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been determined that the activities prepared with Web 2.0 technologies contribute to the creation of a more effective learning environment in line with the interests and wishes of the z-generation students and to transform the learning environments into a more equipped and enjoyable one. Similarly, studies have supported that the activities carried out with web 2.0 technologies contribute to the learning level of students (Arslan & Coştu, 2021;Ergül Sönmez & Çakır, 2021;Açıkgül Fırat & Fırat, 2020;Vanichvasin, 2021;Kazazoğlu & Bilir, 2021;Egüz, 2020;Karakaş & Kartal, 2020;Bolliger & Shephard, 2017;Şahin Topelcengiz & Yıldırım, 2020;Juškeviciene & Kurilovas, 2014;Azid, Hasan, Nazarudin & Ali, 2020;Jong & Tan, 2021). With this thought, it is necessary to use in-class and extra-curricular activities prepared with web 2.0 technologies that support educational environments.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Opetuskäytössä ja erityisesti opetukseen integroituna chattibotit ovat harvinaisia, joten aihepiirin tutkimustakaan ei juuri ole (ks. Vanichvasin 2021). Kieltenopetuksessa chattibotteja on hyödynnetty jonkin verran (Lee, Yang, Shin & Kim 2020, 340), ja tutkimuksenteon opetuksessa niiden on todettu vaikuttavan myönteisesti oppimistuloksiin.…”
Section: Chattibotti Apuopettajana Verkko-opetuksessaunclassified